Manual of clinical behavioral medicine for dogs and cats - Overall, Karen L.
The veterinarian's reliable tool for helping clients resolve pet behavior problems! Written by well-known veterinary behavior specialist Dr. Karen Overall, this comprehensive resource explains the underlying causes of undesirable behaviors in dogs and cats and provides proven behavior modification techniques. A companion DVD offers five in-depth questionnaires to help you gather valuable information from clients, as well as 45 client instruction handouts and a 30-minute video demonstrating behavior modification techniques for clients to use with their pets. From digging and barking to biting and anxiety and everything in between Manual of Clinical Behavioral Medicine for Dogs and Cats has what you need to help clients manage their pets' behavior issues and live with them in harmony